Blockchain-Based Secure Framework for Health Data Sharing - Dubey, Vikas; Mukherjee, Manoj; Yadav, Kavita (International Journal of Unified Research & Development (IJURD), 2025)
Secure sharing of healthcare data is essential for improving clinical outcomes, enabling collaborative research, and ensuring continuity of care. However, traditional centralized systems face challenges related to data privacy, security, and trust among stakeholders. This paper presents a Blockchain-Based Secure Framework for Health Data Sharing that leverages decentralized architecture to ensure secure and transparent data exchange. The proposed system utilizes blockchain technology to maintain an immutable ledger of transactions, ensuring data integrity and traceability. Smart contracts are employed to enforce access control policies, allowing only authorized entities to access sensitive health information. The framework also incorporates encryption techniques to enhance data confidentiality during storage and transmission. Additionally, integration with machine learning techniques supports intelligent data analysis while preserving privacy. Experimental observations indicate that the proposed approach enhances security, reduces the risk of data breaches, and improves trust among healthcare providers and patients. The study highlights the potential of blockchain-based solutions in enabling efficient, secure, and scalable health data sharing, particularly in distributed and resource-constrained healthcare environments.